2003
DOI: 10.1002/jnr.10654
|View full text |Cite
|
Sign up to set email alerts
|

Early NFκB activation is inhibited during focal cerebral ischemia in interleukin‐1β‐converting enzyme deficient mice

Abstract: Our previous study demonstrated that the inhibition of interleukin-1beta (IL-1beta) reduces ischemic brain injury; however, the molecular mechanism of the action of IL-1 in cerebral ischemia is unclear. We are investigating currently the role of NFkappaB during focal cerebral ischemia, using mutant mice deficient in the interleukin-1 converting enzyme gene (ICE KO) in a middle cerebral artery occlusion (MCAO) model. Adult male ICE KO and wild-type mice (n = 120) underwent up to 24 hr of permanent MCAO. Cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Interestingly, TNF-α did not change in caspase-1 -/-mice although ICAM-1 expression (by immunoblotting and immunohistochemistry) was reduced at all time points. NFκB, a transcription factor known to regulate numerous proinflammatory target genes, was reduced in the caspase-1 -/-mice at 2 and 4 hours, but not at later time points; ICAM-1 expression was also reduced in this study [77]. Neither of these studies assessed parameters of protection such as infarct size or neurological score.…”
Section: Genetically Altered Micementioning
confidence: 69%
“…Interestingly, TNF-α did not change in caspase-1 -/-mice although ICAM-1 expression (by immunoblotting and immunohistochemistry) was reduced at all time points. NFκB, a transcription factor known to regulate numerous proinflammatory target genes, was reduced in the caspase-1 -/-mice at 2 and 4 hours, but not at later time points; ICAM-1 expression was also reduced in this study [77]. Neither of these studies assessed parameters of protection such as infarct size or neurological score.…”
Section: Genetically Altered Micementioning
confidence: 69%
“…Mice deficient in IL-1RA show increased ischemic brain damage, further supporting the notion that IL-1 plays a detrimental role in the pathophysiology of stroke (Allan et al, 2005). Furthermore, mice lacking interleukin-1␤-converting enzyme (ICE), also known as caspase-1, showed less ischemic brain injury, edema formation, and inflammatory responses (Huang et al, 2003). Interestingly, this was paralleled by reduced activation of NF-B in electrophoretic mobility shift assays and a significant reduction in the phosphorylation of the RelA subunit.…”
Section: Mechanisms Of Nf-b Activation In Cerebral Ischemiamentioning
confidence: 87%
“…2004). Huang et al . (2003) documented that decreased NF‐κB activity was observed in ischemic ICE null adult mice and suggested that IL‐1 signaling contributes to NF‐κB activation and subsequent ischemic damage.…”
Section: Discussionmentioning
confidence: 99%